EFEKTIVITAS MEDIA E-LEARNING BERBASIS EDMODO TERHADAP HASIL BELAJAR SISWA KELAS V SDN 02 NGABUL JEPARA - Nabila Nur Zahara; Murtono Murtono; Ika Ari Pratiwi (Jurnal Prasasti Ilmu, 2021)
This study aims to analyze the effectiveness of Edmodo-based E-Learning media on the learning outcomes of fifth grade students on the theme of 6 Heat and the Transfer of Indonesian Language and PPKn SDN 02 Ngabul Jepara in the academic year 2020/2021. This research uses pre-experimental designs with one-group pretest-posttest design. The use of Edmodo-based E-Learning media on the learning outcomes of fifth grade students on the theme of 6 Heat and Transfers of Indonesian and PPKn content shows that in the pretest results on Indonesian language content there are 20 students declared complete while on PPKn content 25 students are declared complete and on the posttest results In the Indonesian language content, 34 students were declared complete while in the PPKn content there were 35 declared complete. The statistical test showed that there was the effectiveness of Edmodo-based E-Learning media on the learning outcomes of the theme of 6 Heat and Its Transfer in Indonesian content, the t count was -8.241 and the sig (2-tailed) value was 0.000 less than 0.05 and PPKn was obtained. the result of t count is -9.031 and the sig value (2-tailed) is 0.000 less than 0.05. Based on the results of these statistical tests, it can be concluded that the use of Edmodo-based E-Learning media is effective in using the learning outcomes of fifth grade students on the theme of 6 Heat and the Transfer of Indonesian Language and PPKn content.